IVUS-Guided Zero-Contrast PCI in CKD Patients: Safety and Short-Term Outcome in Patients with Complex Demographics and/or Lesion Characteristics - Prathap Kumar; Blessvin Jino; Ali Shafeeq; Stalin Roy; Manu Rajendran; Sandheep George Villoth (Journal of Interventional Cardiology)
Background. Percutaneous coronary intervention (PCI) in patients with significant renal dysfunction is challenging because of the lesion characteristics and the risk of contrast-induced acute kidney injury (CI-AKI). With the advent of intravascular ultrasound- (IVUS-) guided zero-contrast PCI, outcomes have improved considerably. Objective. To assess the safety and short-term outcomes of IVUS-guided zero-contrast PCI in chronic kidney disease (CKD) patients with complex demographics or lesion morphology. Methods. Patients who underwent IVUS-guided zero-contrast PCI at a tertiary center, from November 2019 to May 2020, were included in this prospective analysis. Clinical characteristics, procedural data, and follow-up data were collected and analyzed. Results. A total of 15 patients (27 vessels), all men (mean age, 70.0 ± 11.0 years), underwent zero-contrast PCI. The mean estimated glomerular filtration rate (eGFR) and serum creatinine were 30.8 ± 7.3 mL/min/1.73 m2 and 2.6 ± 1.3 mg/dL, respectively. The mean BMC2 risk for dialysis was 2.1 ± 1.1%, mean SYNTAX score was 20.3 ± 10.3, and mean left ventricular ejection fraction (LVEF) was 42.4 ± 11.6%. Four patients (26.6%) underwent left main coronary artery (LMCA) PCI including one LMCA bifurcation. One patient underwent chronic total occlusion PCI. Technical and procedural success were 100% without any periprocedural complications. No major adverse cardiovascular events (MACE) were reported, and no patient required dialysis within three months of follow-up. Conclusion. Zero-contrast PCI guided by IVUS is safe in coronary artery disease (CAD) patients with moderate-to-severe CKD. High procedural success without complications can be achieved even in cases with complex clinical characteristics and lesion morphology.